PENGARUH PENGUNGKAPAN ENTERPRISE RISK MANAGEMENT, PENGUNGKAPAN INTELLECTUAL CAPITAL DAN UKURAN DEWAN KOMISARIS TERHADAP NILAI PERUSAHAAN - Ni Ketut Ary Sedani; Putu Cita Ayu (Hita Akuntansi dan Keuangan, 2021)
The purpose of this study is to obtain evidence of the effect of ERM disclosure, IC disclosure and board size on firm value. This research was conducted on property, real estate and construction sector companies in 2015-2018 with 44 populations and 144 samples. The results of this study are multiple linear regression, which shows that enterprise risk management disclosure has a positive and significant effect on firm value, while intellectual capital disclosure and board size do not have a significant effect on firm value.